Why women’s leadership and empowerment are essential today: Innovative concepts from practical action - Zohra, Bitar; Asmaa, Boucif Zineb; El Amir, Raffar Abdelkader (The International tax journal, 2025)
The aim of this paper is to examine the relationship between woman leadership, empowerment and the sustainable economic development, and presents a short review of the literature on the relevance and role of women’s leadership and her economic empowerment. This article discusses: Why Especially Women’s leadership and Empowerment Became Necessary for sustainable economic development? The study is primarily based upon the secondary data. For this extant literature related to the topic from different databases, websites and other available sources were collected. I searched relevant literature in Scopus, science direct, and Google Scholar using specific keywords, e.g., “woman leadership,” “woman empowerment,” “sustainable development,” “economic growth”. A systematic review of collected literature was done in detail.